O lugar do léxico no ensino de língua portuguesa: análise da abordagem lexical em um livro didático do ensino médio. - Silva, Severino Carlos da (2020)
It is believed that a broader knowledge of the lexicon is paramount for a learner to go beyond the common repertoire, building favorable environments for proper communication in different social contexts. (LEWIS, 1993, 1997, 2000; LEFFA, 2000). In this perspective, knowing the lexicon well is an indispensable condition for a richer communicative competence in BP (ANTUNES, 2012, TEODORO, 2018). However, although the relevance of such knowledge is a consensus among the majority of professionals working in the area, there is a feeling that it has been minimized, given that it seems to be present only in most teachers’ rhetoric, as well as absent not only from the initial and continuing education of teachers, but also from syllabus that are part of Brazilian Portuguese Textbooks (BPTs). This work is characterized by a qualitative documentary research, aiming to investigate the place occupied by the lexicon in BPT through the analysis of exercises of this linguistic knowledge. With this purpose, the 9th edition of the “Português: Linguagens” (HS) collection, by William Roberto Cereja and Thereza Anália Cochar Magalhães, was selected among the ten collections recommended by PNLD 2015. The collection was published by Editora Saraiva and used from 2015 to 2017. After selecting it, we identified the vocabulary exercises in the textbooks, analyzed the corpus, and made a comparison between the space given to the lexicon and to grammar in the collection. Based on the guidelines of Lexicology (ANTUNES, 2012; CARVALHO, 2009, 2011; BIDERMAN, 2001; TEODORO, 2018) and the Lexical Approach (LEWIS, 1993, 1997, 2000; LEFFA, 2000; ZIMMERMAN, 1997, MELKA, 1997; BINON , 2000; ELLIS, 1997 and others), this research also alludes to the Common European Framework of Reference for Languages (CEFR) and the Framework of Reference for the Teaching of Portuguese Abroad (QuaREPE). It is observed that the Lexical Approach (LA), the CEFR and the QuaREPE place lexical competence at the top of those identified as the most relevant ones to the knowledge of a language, defending a language concept based on “chunks” (lexical portions). It is seen as a lexicalized and non-grammatical phenomenon, differently from what happens in traditional teaching, in which knowing the grammar is often mistaken for knowing the language. The integrated teaching of lexical-grammatical patterns (lexicon + grammar) is defended in detriment of a dichotomous approach (lexicon x grammar). The option of adopting LA (which places the lexicon at the center of the teachinglearning process), even if conceived for the teaching of the English language, is justified by the lack of a national approach to work on PL lexicon (BORTONI-RICARDO, 2005; SEIDE; DURÃO, 2015). Our conclusion is that BPTs still focus on the study of grammar (language as a code), neglecting the study of the lexicon. Moreover, when this study is present, words continue to be seen in isolation, detached from their context, with only few exceptions. In the end, we hope this research will fill some gaps in the existing investigations on the theme, leaving a contribution that pique the interest of other researchers who address issues regarding the way lexicon is taught in BPT. We also hope it sparks the interest of HS teachers, mainly by pointing out paths that can be followed in order to obtain better results in their teaching practice, especially when it comes to teaching PL lexicon.